PERSEPSI SISWA KELAS 3 SMAN 1 BANGKINANG TENTANG MOTIVASI ORANG TUA MEREKA UNTUK MELANJUTKAN PENDIDIKAN ANAKNYA KE PERGURUAN TINGGI - Khairil Pajri; Aswandi Bahar; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the motivation of their parents to continue their education to college. The formulation of the problem in this research is Is the perception of students of grade 3 SMAN 1 Bangkinang about their parents' motivation to continue their education to university, is high ?. The purpose of this research is to know the perception of 3rd graders of SMAN 1 Bangkinang about the motivation of their parents to continue their education to university. Population taken in this research is student of class 3 SMAN 1 Bangkinang. The number of students of grade 3 SMAN 1 Bangkinang is 62 students. So the sample in this study amounted to 38 students and test samples of 20 people, as for sampling with simple random sampling technique (sampling randomly simple). Instrument data collection in this research is by questionnaire technique with 42 items statement. After the questionnaire was tested, 3 items were invalid, and the researcher discarded all invalid statements. The results of this study indicate the perception of grade 3 students of SMAN 1 Bangkinang about the motivation of their parents to continue their education to university in the view motivation is intrinsic motivation with percentage of 75%, so that intrinsic motivation is more dominant than extrinsic motivation.Keywords: Perception, motivation, College